Necesidad de incorporar a la posesión efectiva como una forma de obtener el dominio cuando se es único y universal heredero - Campoverde Villavicencio, Jorge Fabricio (2022)
The present paper seeks to modify the status quo of effective possession in Ecuadorian law, in the case of the sole and universal heir, as it is a vital process to acquire the domain and not only of possession of the property of the deceased. In addition, because it seeks to solve, the multiple procedures that the heir must perform this are the inventory and the partitioning of them. Valid possession is express acceptance of the inheritance, is personal, valid possession cannot be requested by others or prescribed by a third party, and in the case of minors or court orders, the only appropriate representative is the legal representative. It is proindiviso, that is, all the assets of the deceased active and passive, and cannot be effectively possessed over certain assets, because the inheritance is universal, including assets and liabilities. Now what happens when the deceased leaves a single universal heir of all his property, so that the latter has access to the inheritance opened after the respective effective possession, according to our current Civil Code there is no express rule to obtain title in this specific case, if not what it says that the effective possession is not just title to be made the respective inventory and then the partition is this judicially or extrajudicially. In the present work, the scientific method was used giving a qualitative approach, the legal normative, legal dogmatic and legal jurisprudential mode and the technique of documentary analysis were used. With regard to the approach to the problem when the sole and universal heir is involved, it is necessary to inventory assets and award them, which entails formality, expenses and procedural burden to the judicial units, which can be avoided with effective possession. This is inventory and then the partition be it judicial or extrajudicial, so that you make inventory of the property left by the causative and the partition if there are no more heirs. It will be possible for the actual possession to be considered as a title transfer in case of being the sole universal heir and the latter can dispose of the property left by the deceased without the need to make an inventory, with whom the partition is made be it judicial or extrajudicial if there are no more heirs, because this issue has not been taken into account in Ecuadorian legislation, in the case of being sole and universal heir this will be able to dispose of the goods left by the deceased only with the effective possession being taken into account as transferable title of domain in our legislation.